DETERMINAN TATA KELOLA TEHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH ( STUDI KASUS PADA BKAD KOTA MALANG) - Sati, Donisia; Fariz Irianto, Mochamad; Amir Fikri Anas, Dimas Emha (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
This research aims to test the determination of governance on the quality of Malang City regional government financial reports. The dependent variable in this research is the quality of financial reports (Y). This research uses accountability, transparency, human resource competence, and internal control system as independent variables (X). The data used in this research is primary data. The data collection method uses a questionnaire which is announced directly to respondents. The sampling technique used saturated sampling (total sampling and a sample of 58 employee respondents was obtained at the Malang City BKAD Office. The results of this research show that accountability, transparency, human resource competence and the internal control system simultaneously (together) have a significant effect on quality of financial reports, Accountability has a positive and significant effect on the quality of financial reports, Transparency has a positive and significant effect on the quality of financial reports, Human resource competency has a positive but not significant effect on the quality of financial reports and Internal control systems have a positive and significant effect on the quality of financial reports.